Prevention of Secondary Victimisation within the Ukrainian Barnahus Model in the Context of European Standards of Justice - N. P. Korol; O. V. Korol (Bulletin of Kharkiv National University of Internal Affairs)
The article states that in all cases where a child is subjected to abuse, authorised entities, including courts, must ensure that the child's interests are protected and their rights are upheld. Anyone involved with a child is responsible for performing their duties properly and effectively, in a friendly manner, bearing in mind the priority of the child's interests.